EFFECT OF SUPPLEMENTATION DATE PALM POLLEN ON SOME PHYSIOLOGICAL AND REPRODUCTIVE TRAITS OF JAPANESE QUAIL BIRDS (Coturnix Coturnix japonica) - & et al., Al-Salhie (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted at quail's field of Agriculture Collage/University of Basrah for the period from 21/8/2016 to 21/10/2016 to examine the effect of adding date palm pollen to feed on some Physiological and reproductive traits of Japanese quail birds. The study was included (240) chicks one day old of brown quail. They were randomly distributed to five treatments each treatment contained 48 chicks with three replicates each one 16 chicks, the treatments as the following, first (T1), second (T2), third (T3), fourth (T4) and fifth (T5) in these treatments, were fed on a diet supplemented the date palm pollen amount (0, 250, 500, 750 and 1000 mg/kg). The results showed a significant increase in the relative weights of the testicular, ovary and oviduct of T5 compared to other treatments at the age of 30 and 60 days, As well as a significant improvement in the number and diameter of primary ovarian follicles in the females and significantly improved in the seminiferous tubules diameter and germinal layer thickness and a significant reduction of the seminiferous tubules lumen diameter in males at the same ages, There was a significant increase in hormones (testosterone, estrogen, FSH and LH) in the serum of T5 compared to other treatments of males and females at the age of 30 and 60 days. In conclusion, the date palm pollen was improved of Physiological and reproductive traits of Japanese quail.